Keabsahan Tanda Tangan Elektronik oleh Notaris - Louis Figgo; Bambang Eko Turisno (LPPM Universitas Ekasakti Padang, 2023)
This research examines legal studies related to the validity of electronic signatures by Notaries in Indonesia. A notary is a public official who is responsible for making a deed. If in carrying out their profession it is proven that they have committed mistakes and misuse, the notary will be subject to sanctions, both civil, administrative and criminal sanctions.The research method used is normative juridical study, namely research studies originating from legal sources such as laws and regulations, and expert opinion to research studies related to the title chosen by the researcher. The result of this research is that it is known that as a public official, a notary has a position in making authentic deeds. The rapid development of information technology has affected the legal profession, one of which is the notary profession. The influence on the notary profession can be seen with the concept of a cyber notary. Electronic signatures already have provisions in the ITE Law. This is reinforced by UUJN-P Article 15 paragraph 3 which gives authority to certify electronic transactions. However, it is continued in Article 16 paragraph 1 which states that at the time of signing this, the notary must be physically present. This makes the notary's signature electronically receive recognition from the law, it's just that no law regulates it specifically and in detail.